2020
DOI: 10.1007/s10461-020-03005-x
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Effects of the COVID-19 Pandemic on Youth Living with HIV in Western Kenya

Abstract: The objective of this study was to assess psychosocial effects of COVID-19 among adolescents living with HIV (ALHIV) in Kenya and to assess the feasibility of conducting behavioral surveys by phone. We adapted our protocol to administer telephone rather than in-person follow-up surveys and included questions about COVID-19. The majority of participants (99%) reported having heard of COVID-19; 23% reported no longer being able to go outside, 17% reported that they could no longer go to their regular clinic for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 4 publications
2
84
0
Order By: Relevance
“…Various screening tools based on different cut‐off scores were also used to measure depressive (Table 2) or anxiety symptoms (Table 3). These screening tools included the 9‐item patient health questionnaire [76] used in six studies [49,53,57,60,77, 78], the centre for epidemiologic studies depression scale [79] used in four studies [51,54,56,62], the child depression inventory [80] used in four studies [58,59,81,82], Beck’s depression inventory [83] used in three studies [48,61,84], the revised children’s depression rating scale [85] used by Kim et al . [28], the hospital anxiety and depression scale [86] used by Sale & Gadanya [47], Reynold’s adolescent depression Scale [87] used by Paul et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various screening tools based on different cut‐off scores were also used to measure depressive (Table 2) or anxiety symptoms (Table 3). These screening tools included the 9‐item patient health questionnaire [76] used in six studies [49,53,57,60,77, 78], the centre for epidemiologic studies depression scale [79] used in four studies [51,54,56,62], the child depression inventory [80] used in four studies [58,59,81,82], Beck’s depression inventory [83] used in three studies [48,61,84], the revised children’s depression rating scale [85] used by Kim et al . [28], the hospital anxiety and depression scale [86] used by Sale & Gadanya [47], Reynold’s adolescent depression Scale [87] used by Paul et al .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐nine studies reported the prevalence of either major depression or depressive symptoms [45‐67,77,78,81]. Of these, seven studies [50,55,58,59,65,66,78] additionally reported the prevalence of anxiety or its symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the rapid spread of the virus and an exponential increase in cases, a strategy of mass quarantine has been implemented globally. Despite these measures to aid healthcare, a resultant disturbing impact on mental health could arise among PLWHA [ 48 ]. It has been evidenced that psycho-social depression could have a negative impact on health and behavior, and is associated with poor health outcomes [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 52 People with HIV Nineteen studies assessed PLHIV. [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Three modelling studies predicted a significant increase in HIV-related deaths in African countries due to treatment disruption with the pandemic. [61][62][63] A US retrospective observational quantitative study found that shelter-inplace orders had a negative impact on antiretroviral therapy adherence, especially among homeless PLHIV.…”
Section: General Publicmentioning
confidence: 99%